The Resilience of Jengkingan Culture Amidst the Dominance of the Labor Wage System in Farming Communities - Nicka Lovelya Khailaputri; Novia Wahyu Wardhani (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Modernization and the growing dominance of wage labor systems have eroded mutual aid practices in agrarian societies, yet existing studies often overlook the rational reasons for cultural preservation. Drawing on social exchange and social capital theories, this study addresses this gap by examining why the Jengkingan culture persists as a reciprocal agricultural practice. The research aims to analyze the resilience of Jengkingan and identify the factors that support or inhibit it. A qualitative case study approach was employed, using observation, interviews, and documentation, with data analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal that Jengkingan survives because it is economically efficient and strengthens social solidarity through non-material social exchange and robust social capital. Supporting factors include kinship ties, trust, reciprocity, and local social conditions, while time constraints, shifting mindsets among youth, and minimal leadership roles act as inhibitors. The study concludes that Jengkingan can be integrated into modern life as a rational choice without losing its cultural essence, and recommends further research on its effectiveness in farming communities. Modernisasi dan dominasi sistem upah tenaga kerja telah menurunkan intensitas praktik gotong royong di masyarakat agraris, namun studi yang ada sering mengabaikan alasan rasional di balik pelestarian budaya tersebut. Menggunakan teori pertukaran sosial dan modal sosial, penelitian ini mengkaji mengapa budaya Jengkingan bertahan sebagai praktik pertanian berbasis timbal balik. Tujuannya untuk menganalisis ketahanan budaya Jengkingan serta faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif studi kasus dengan observasi, wawancara, dan dokumentasi, dianalisis melalui model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa Jengkingan bertahan karena dianggap efisien secara ekonomi dan memperkuat solidaritas sosial melalui pertukaran sosial non-material serta modal sosial yang kuat. Faktor pendukung meliputi ikatan kekerabatan, kepercayaan, timbal balik, dan kondisi sosial masyarakat, sementara faktor penghambatnya adalah keterbatasan waktu, pergeseran pola pikir generasi muda, serta minimnya peran tokoh masyarakat. Penelitian ini menyimpulkan bahwa budaya Jengkingan dapat diintegrasikan dalam kehidupan modern sebagai pilihan rasional tanpa menghilangkan esensi budayanya, dan merekomendasikan penelitian lebih lanjut mengenai efektivitas praktik budaya ini pada masyarakat petani.